2020
DOI: 10.1016/j.quageo.2020.101094
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of multiple luminescence chronometers at Voordrag, South Africa

Abstract: Highlights1. Existing radiocarbon and feldspar IRSL50 ages for Voordrag are incorrect 2. IRSL50 signal affected by anomalous fading 3. Single grain quartz OSL and K-feldspar post-IR IRSL ages match 4. Saturation of OSL signal identified using In/I0 ratio and proportion of saturated grains 5. Paired quartz/feldspar measurements can identify effect of saturation on quartz OSL signal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Brook et al, 2006; Grodek et al, 2013; Srivastava et al, 2006). Where possible, depositional ages are based on single grain analysis, as it allows for the well‐bleached component to be isolated (Colarossi et al, 2020; Duller, 2008). Single grain analysis shows that detectable signals derive from 2 to 3% of grains, and as small aliquot 180–210 μm multigrain discs contain ~68 grains per disc (Burow, 2020; Heer et al, 2012), it is likely that D e s are derived from only one to two grains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brook et al, 2006; Grodek et al, 2013; Srivastava et al, 2006). Where possible, depositional ages are based on single grain analysis, as it allows for the well‐bleached component to be isolated (Colarossi et al, 2020; Duller, 2008). Single grain analysis shows that detectable signals derive from 2 to 3% of grains, and as small aliquot 180–210 μm multigrain discs contain ~68 grains per disc (Burow, 2020; Heer et al, 2012), it is likely that D e s are derived from only one to two grains.…”
Section: Resultsmentioning
confidence: 99%
“…As the ability to radiometrically date geomorphological records has improved (e.g. Colarossi et al, 2020), and the controls on the formation of landforms by sediment transport are understood (e.g. Larkin et al, 2020; Mayaud et al, 2017; Paola et al, 2009), so has the contribution of geoproxies such as fluvial records to assessing the amplitude and nature of hydrological change (Stone & Thomas, 2013; Thomas & Burrough, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the 3-mm aliquot is too large to obtain the true dose for the young poorly bleached sediments. Some studies have shown that the D e of small aliquots (~2 mm or >100 grains) is overestimated compared Frontiers in Earth Science frontiersin.org with the expected D e , as the number of grains on the small aliquots is too large to distinguish the well-bleached population, although they used the lowest 5% or MAM (Wu et al, 2010;Colarossi et al, 2020). For the wellbleached sample DSG6, the D e distributions have no dependency on the aliquot sizes and age models except the lowest 5% D e of the 1-mm aliquot is negative (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Optically stimulated luminescence (OSL) dating measurements of quartz grains, especially from older samples, often include data from grains with saturated palaeodoses (e.g. Thomsen et al, 2016;Colarossi et al, 2020). The proportion of saturated grains can vary substantially between samples and is influenced not only by the magnitude of each grain's equivalent dose (D e ), but also by the dose at which each grain's OSL signal saturates.…”
Section: Introductionmentioning
confidence: 99%
“…Dose recovery experiments suggest that measurements with more than 50% of saturated grains may not provide accurate dose estimates (Duller 2012), and some studies of natural samples have attributed underestimations of single grain ages relative to multi-grain ages to the effects of saturated grains (e.g. Thomsen et al, 2016;Colarossi et al, 2020). If these saturated grains contain useful chronological data, more accurate D e values, and hence ages, could potentially be obtained if these grains could be incorporated into the analysis.…”
Section: Introductionmentioning
confidence: 99%